Effect of Bitter Melon (Momordica charantia) on Caspase - 3 Expression and the number of Apoptotic Cells in T47D Cancer Cell Culture (Bangladesh Journal of Medical Science, 2026)
Background Cancer is reason death number two in the world. Bitter melon has component bioactive that shows potency activity anti-cancer. Extract bitter melon fruit is known as anti- cancer in human breast cancer cells, MCF-7 and MDA-MB-231, Objectives: Objective study in vitro, knowing caspase 3 expression and amount cells undergoing apoptosis in the given T47 D cell culture extract bitter melon. Methodology Study experimental laboratory with post-test only randomized control group design.T47 D cell culture samples group control and group treatment each as many as 3 wel with density 5x10 4 cells /100 μl, each well filled with T47 D cell culture density cells 5x10 4 cells /100 μl, given extract ethanol bitter melon fruit dose ½ IC 50. IC50 and 2 IC50, incubation for 24 hours. After 24 hours, the Coverslip is removed and carried out painting immuno cytochemistry for see expression caspase -3 and Fluocytometry for see the number of cells undergoing apoptosis Data on caspase 3 expression were tested with One-way anova test and Post hoc test. Fluocytometry data, served in a way descriptive. Result The IC50 dose resulted in a value of 269.4 μg/mL. The average expression of caspase-3 in T47D cell cultures was 15.23+2.05 in the control group, 21.17+1.44 in the half IC50 dose group, and the highest in the IC50 dose group was 23.28+2.25. The lowest expression of caspase-3 in T47D cells was found in the group with a dosage of 2 IC50, which was 7.58+0.68. The amount of apoptotic cells with Fluocytometry was increased expression . The highest amount of apoptotic cells was found in the 2 IC50 dose group, whereas it was the lowest in the 1/2 IC50 dose group. Conclusion Ethanol extrac of bitter melon fruit has anti cancer activity.BJMS, Vol. 25 No. 02 April’26 Page: 558-565